Rekonstruksi Kesenian dalam Tradisi Resam Munoling Etnik Gayo Kabupaten Aceh Tengah - Fathia Juhra; Neva Nabila; Cut Thiya Arifa; Ananda Zhafira Mazaya; Gustiana Gustiana; Irma Rahmayani; Rida Safun Selian (Jurnal Riset Rumpun Seni, Desain dan Media, 2023)
The Resam Munoling tradition is a cultural heritage of the Gayo community in Kebayakan, Central Aceh, reflecting mutual cooperation (gotong royong) and artistic values in rice harvesting. However, modernization has caused this tradition to fade, particularly the traditional singing elements and the accompaniment of canang music. This descriptive qualitative study aims to analyze the strategy of reconstructing the arts within Resam Munoling to ensure they remain preserved and relevant. Data were collected through observation, in-depth interviews, and documentation with artists, farmers, and community leaders in Kebayakan Subdistrict. The study identified five key reconstruction strategies: mapping and documentation, training, artist collaboration, technology utilization, and government support. The results indicate that reconstruction can be achieved by documenting artistic elements (music, songs, costumes), involving local artists for regeneration, and utilizing digital technology for promotion. Government support through policies, funding, and cultural festivals is also highly significant. This reconstruction not only revives traditional art but also strengthens the cultural identity and social solidarity of the Kebayakan community